Transgender Status, Gender Identity, and Socioeconomic Outcomes in the United States. (May 2020) - Carpenter, Christopher S.; Eppink, Samuel T.; Gonzales, Gilbert
This article provides the first large-scale evidence on transgender status, gender identity, and socioeconomic outcomes in the United States, using representative data from 35 states in the Behavioral Risk Factor Surveillance System (BRFSS), which asked identical questions about transgender status and gender identity during at least one year from 2014 to 2017. More than 2, 100 respondents, aged 18 to 64 years, identified as transgender. Individuals who identify as transgender are significantly less likely to be college educated and less likely to identify as heterosexual than are individuals who do not identify as transgender. Controlling for these and other observed characteristics, transgender individuals have significantly lower employment rates, lower household incomes, higher poverty rates, and worse self-rated health compared to otherwise similar men who are not transgender.